Radiotherapy refusal in breast cancer with breast-conserving surgery - Liu, Jiameng; Zhu, Zhanlin; Hua, Zhipeng; Lin, Weijie; Weng, Yiyin; Lin, Juli; Mao, Hehui; Lin, Lifen; Chen, Xuming; Guo, Jujiang (Radiation oncology (London, England), 2023)
Although radiotherapy after breast-conserving surgery has been the standard treatment for breast cancer, some people still refuse to undergo radiotherapy. The aim of this study is to identify risk factors for refusal of radiotherapy after breast-conserving surgery. To investigate the trend of refusing radiotherapy after breast-conserving surgery in patients with breast cancer using the Surveillance, Epidemiology, and End Results database. The patients were divided into radiotherapy group and radiotherapy refusal group. Survival results were compared using a multivariate Cox risk model adjusted for clinicopathological variables. Multivariate logistic regression was used to analyze the influencing factors of patients refusing radiotherapy after breast-conserving surgery and a nomogram model was established. The study included 87,100 women who underwent breast-conserving surgery for breast cancer between 2010 and 2015. There were 84,948 patients (97.5%) in the radiotherapy group and 2152 patients (2.5%) in the radiotherapy refusal group. The proportion of patients who refused radiotherapy after breast-conserving surgery increased from 2.1% in 2010 to 3.1% in 2015. The Kaplan-Meier survival curve showed that radiotherapy can improve overall survival (p < 0.001) and breast cancer specific survival (p < 0.001) in the patients with breast-conserving surgery. The results of multivariate logistic regression showed that age, income, marital status, race, grade, stage, subtype and chemotherapy were independent factors associated with the refusal of radiotherapy. Postoperative radiotherapy can improve the benefits of breast-conserving surgery. Patients with old age, low income, divorce, white race, advanced stage, and no chemotherapy were more likely to refuse radiotherapy.